Implementation of balance control on terrain quadruped traversal - Del Rosario, Jay Robert B. (Animo Repository, 2016)
Implementation of balance control and development of an android application based remote control for a three (3) Degrees of Freedom quadruped robot is proposed. Balance control is achieved by shifting the quadruped's center of gravity using a proposed gait sequence and accelerometer sensor reading for tilt compensation while the development of the android application is through the use of Android Eclipse SDK. This study provided a simple yet effective approach in balance control. The implementation maintained the deviation in acceleration in the 1.5 m/s2. Data and results gathered are presented. © 2015 IEEE.